Beyond Stereotypes American Jews and Sports in the Twentieth Century - Sclar, Ari (Purdue University Press, 2014)
In the decades after the Civil War, sports slowly gained a prominent position within American culture. This development provided Jews with opportunities to participate in one of the few American cultures not closed off to them. Jewish athleticism challenged anti-Semitic depictions of Jews' supposed physical inferiority while helping to construct a modern American Jewish identity. An Americanization narrative emerged that connected Jewish athleticism with full acceptance and integration into American society. This acceptance was not without struggle, but Jews succeeded and participated in the American sporting culture as athletes, coaches, owners, and fans. The diversity of topics in this volume reflect that the field of the history of American Jews and sports is growing and has moved beyond the need to overcome the idea that Jews are simply "People of the Book." The contributions to this volume paint a broad picture of Jewish participation in sports, with essays written by respected historians who have examined specific sports, individuals, leagues, cities, and the impact of sport on Judaism. Despite the continued belief that Jewish religious or cultural identity remains somehow distinct from the American idea of the "athlete," the volume demonstrates that American Jews have had a tremendous contribution to American sports-and conversely, that sports have helped construct American Jewish culture and identity.